ANÁLISE DE REQUISITOS PARA CONTRATAÇÃO DE OBRAS PÚBLICAS BASEADA EM MODELOS BIM - Dadam, Talita; Carvalho, Michele Tereza Marques (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The use of Building information modeling (BIM) represents a change in the working methodology of construction professionals. The dissemination of this technology in the public sector will help to obtain a better application of the resources and to provide transparency and control of the expenses with its buildings. With this vision, the Brazilian Government established a strategic committee to implement BIM with the purpose of proposing the national dissemination strategy. This committee published, in November 2017, a compilation composed of six volumes with guidelines and, among them, one orienting the contracting of BIM projects of architecture and engineering. However, for the success of this contracting, some requirements must be clearly and objectively stated in the contracts signed between the public administration and the contracted professional/company so that responsibilities are guaranteed in all phases of contracting and throughout the life cycle of the building. In this work, we sought to relate the contractual requirements addressed in this volume with the requirements identified in international publications.